Higher Education System in Portugal; An Exploratory Study about the Challenges Setting by the New Bologna Paradigm - Saraiva, Margarida (2012)
Total quality management is a process based on a “to do differently” strategy. This strategy implies trying to achieve continuous improvement by sharing responsibilities reducing misused resource and meeting customer’s expectations. Typically, Total Quality Management is implemented in industry and services using a group of principles. The implementation of such principles guides the organizations towards the improvement of quality standards. Deming contributed to the total quality management process by proposing the set of principles and techniques that helps organisations to improve their quality process. We implement the total quality management principles inn two Portuguese high education institutions: ISCTE and University of Évora. We use separate questionnaires in order to verify if the techniques of the Total Quality Management, proposed by Deming, which were applied in Japanese and US companies, could be applied similarly in Portuguese high education institutions. Likewise for industrial companies, application of Total Quality Management techniques may help higher education institutions in their adaptation to the constantly changing education environment. The improving of quality in higher education will result in a general quality improvement of people’s skills which ultimately will improve the level of efficiency contributing to the development of markets and the economy. The results of this study show a set of difficulties as well as benefits from implementation of Total Quality Management, which may be a consequence of the cultural environment of the institutions. This study concludes that the two higher education institutions can still improve the application of the 14 principles proposed by Deming, and that correct application of these principles may permit them to evolve to the excellence level. However, it is important to notice that the principles should be applied in a flexible way and in agreement with the specific needs of each organization.